Komunikasi Antar Pribadi Dalam Mempertahankan Kepuasan Pelanggan - Nurhawati Simamora; Setiamenda Ginting; Rachel Mia L. Lumbantoruan; Sinilia Bohalima; Desti Murni Telaumbanua (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2023)
Communication is a basic human activity, by communicating humans can relate to each other in everyday life wherever humans are. Interpersonal communication is communication between people face-to-face, which allows each participant to capture other people's reactions directly, both verbally and non-verbally. Interpersonal communication, as communication between the communicant and the communicant, is considered the most effective type of communication in an effort to change attitudes, opinions or behavior. This research discusses interpersonal communication to increase customer satisfaction with services. This research aims to find out how interpersonal communication works to determine the level of customer satisfaction, using a humanitarian approach, namely openness, empathy, supportiveness, positivity and equality. This research design is descriptive research with a qualitative approach.